Distinguishing Software Aging from Stability in Open Source Projects: An Empirical Analysis of Activity Indicators - Sirqueira, Tassio; Faciroli, Jessica; Werneck, Vera (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Open-source software projects may experience variations in development activity over time. However, a decline in activity does not necessarily indicate software aging, as mature projects may require fewer changes over time. This study aims to distinguish software aging from stable maturity by analyzing activity indicators empirically. We conducted a longitudinal analysis of three open source projects, examining monthly trends in commits, active contributors, issues, and releases. The results show that stable projects exhibit low but consistent activity, whereas aging projects are characterized by abrupt and sustained declines across multiple indicators. The joint analysis of longitudinal activity indicators enables distinguishing between stability and software aging.